Structural analysis of an Asterias rubens peptide indicates the presence of a disulfide‐directed β‐hairpin fold - Rozita Takjoo; David T. Wilson; Justine Le Quilliec; Casey A. Schmidt; Guangzu Zhao; Michael J. Liddell; Naeem Y. Shaikh; Kartik Sunagar; Alex Loukas; Michael J. Smout; Norelle L. Daly (FEBS Open Bio)
Sea stars are an abundant group of marine invertebrates that display remarkably robust regenerative capabilities throughout all life stages. Numerous proteins and peptides have been identified in a proteome study on the coelomic fluid (biofluid) of the common sea star Asterias rubens, which appear to be involved with the wound‐healing response in the organism. However, the three‐dimensional structure and function of several of these injury‐responsive peptides, including the peptide KASH2, are yet to be investigated. Here, we show that the KASH2 peptide adopts a disulfide‐directed β‐hairpin fold (DDH). The DDH motif appears to be evolutionarily related to the inhibitor cystine knot motif, which is one of the most widespread disulfide‐rich peptide folds. The DDH motif was originally thought to be restricted to arachnids, but our study suggests that as a result of convergent evolution it could also have originated in sea stars. Although the widely conserved DDH fold has potential cross‐phyla wound‐healing capacity, we have shown that KASH2 does not enhance the proliferation of human fibroblasts, a simple method for wound‐healing re‐epithelialisation screening. Therefore, additional research is necessary to determine the role of KASH2 in the sea stars.